Optimizing electronic archive management through information and communication technology for educational SDGs advancement - A. Sobandi; A. Adman; Imaniyati, Nani (LPMPP Universitas Negeri Yogyakarta, 2025)
The digital transformation in information and communication technology (ICT) has significantly influenced archive management in educational institutions. This study aims to explore how electronic archive systems are optimized to improve administrative efficiency and educational governance. Using a qualitative literature-based approach, the paper analyzes the concepts, systems, and legal aspects of electronic archive implementation. The findings reveal that institutions are shifting from manual to digital systems, leading to improved accessibility, transparency, and sustainability. This shift is crucial because effective electronic archive management enhances institutional responsiveness and aligns with the demands of modern education. The impact extends to strengthening digital literacy, ensuring long-term access to academic records, and supporting Sustainable Development Goals (SDGs), particularly Goal 4 (Quality Education) and Goal 16 (Peace, Justice, and Strong Institutions). Therefore, educational organizations must adapt strategically to ICT to maintain relevance and institutional resilience.